Evaluation of the frequency of mucous retention cysts in the maxillary sinus in a Turkish population using cone-beam computed tomography - Lacin, Nihat; Tatar, Birkan (Makara Journal of Health Research, 2019)
Background: Mucous retention cyst (MRC) of the maxillary sinus (MS) is an asymptomatic pathology generally found during routine radiographic examination. This study aimed to investigate the frequency of MRCs in the MS from a Turkish population using randomly selected cone-beam computed tomography (CBCT) images. Methods: CBCT images of randomly selected systemically healthy subjects (n = 300; of which 156 were men and 144 were women with a mean age of 40.18 [age range: 18–65 years]) were included in this retrospective study. The images were evaluated, and MRC was detected as a dome-shaped radiopaque lesion on the floor or walls of the MS. Results: MRC was detected in 30 (10%) of 300 patients via CBCT imaging; 14 patients had bilateral MRC and 16 had unilateral MRC. The cysts were detected on CBCT images obtained from 17 men and 13 women. No significant differences were observed in the incidence of MRC based on location (right or left side) and gender (p > 0.05). Conclusions: CBCT is a useful tool that facilitates three-dimensional evaluation of pathologies, such as MRCs, in the MS.